2015
DOI: 10.1371/journal.pone.0143215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Overweight and Obesity among Children Aged 6–59 Months in Cameroon: A Multistage, Stratified Cluster Sampling Nationwide Survey

Abstract: BackgroundChildhood obesity is one of the most serious public health challenges of the 21st century. The prevalence of overweight and obesity among children (<5 years) in Cameroon, based on weight-for-height index, has doubled between 1991 and 2006. This study aimed to determine the prevalence and risk factors of overweight and obesity among children aged 6 months to 5 years in Cameroon in 2011.MethodsFour thousand five hundred and eighteen children (2205 boys and 2313 girls) aged between 6 to 59 months were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
61
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 41 publications
(60 reference statements)
18
61
7
1
Order By: Relevance
“…This prevalence was higher than the previous Cameroonian (8.0%) study [15] and others sub-Saharan African studies done in Ivory Coast (4.4% in 2012), in Nigeria (6.3% in 2013),in Senegal (6.8% in 2013), and Democratic Republic of Congo (5.6% in 2014) [18]. Many reason can justified this great prevalence, the small sample size, the definition used, the age of participants and the socio-economic status.…”
Section: Discussion:-contrasting
confidence: 79%
See 1 more Smart Citation
“…This prevalence was higher than the previous Cameroonian (8.0%) study [15] and others sub-Saharan African studies done in Ivory Coast (4.4% in 2012), in Nigeria (6.3% in 2013),in Senegal (6.8% in 2013), and Democratic Republic of Congo (5.6% in 2014) [18]. Many reason can justified this great prevalence, the small sample size, the definition used, the age of participants and the socio-economic status.…”
Section: Discussion:-contrasting
confidence: 79%
“…Developing countries are facing the double burden of under nutrition over nutrition and the extent of the problem remains unknown. Projections show that prevalence among children of less than 5 years) obesity will attend the magnitude of 12.7% in Africa by 2020 [14] In Cameroon, scarce childhood obesity data are available [15]. This study was carried out to estimate the prevalence of overweight and obesity among rural preschool children of 2 to 5years…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Regarding pre‐partum maternal weight, three studies found relationships between BMI and childhood obesity, and seven studies reported associations between maternal obesity and childhood obesity. In terms of post‐partum maternal weight, childhood obesity was associated with maternal BMI and maternal obesity (43,44,48,56,77,80,87,104,107,113,123,144,147,148,156,159,167,169,183,184,185,193,198,201,202,32,194,206). There was also a linear relationship between gestational weight gain and childhood obesity , particularly when gestational weight gain was ≥15 kg .…”
Section: Resultsmentioning
confidence: 93%
“…Two studies reported conflicting findings regarding obesity risk and type of school (private versus public school). Other studies reported the following factors (potential proxies for socioeconomic status) as being associated with childhood obesity: fetal exposure to music , living in an Eastern compared to a Western European county , living in a grassfield area compared to a forest area in Cameroon , exposure to English television , and stunted growth .…”
Section: Resultsmentioning
confidence: 99%
“…Smoking was self-reported by mothers and was defined as smoking during pregnancy. As an individual factor, two studies identified a statistically significant correlation between higher maternal educational attainment and obesity in preschool children [14,15]. The maternal influence of smoking was established as a contributor along with LGA to predict childhood obesity, however, the findings did not discuss the relationship of maternal influences of smoking and SGA as a predictor for childhood obesity.…”
Section: Maternal Influencesmentioning
confidence: 94%